Conceptions of Critique in Modern and Contemporary Philosophy
X, 270 p.
Keywords: Does philosophical critique have a future? What are its possibilities, limits and presuppositions? This collection by outstanding scholars from various traditions, responds to these questions by examining the forms of philosophical critique that have shaped continental thought from Spinoza and Kant to Marx, Foucault, Derrida and Rancière.